Behaviour change interventions: getting in touch with individual differences, values and emotions. (28th December 2020) - Strömmer, Sofia; Lawrence, Wendy; Shaw, Sarah; Correia Simao, Sara; Jenner, Sarah; Barrett, Millie; Vogel, Christina; Hardy-Johnson, Polly; Farrell, David; Woods-Townsend, Kathryn; Baird, Janis; Morrison, Leanne; et al.
Abstract: Systematic reviews and meta-analyses suggest that behaviour change interventions have modest effect sizes, struggle to demonstrate effect in the long term and that there is high heterogeneity between studies. Such interventions take huge effort to design and run for relatively small returns in terms of changes to behaviour. So why do behaviour change interventions not work and how can we make them more effective? This article offers some ideas about what may underpin the failure of behaviour change interventions. We propose three main reasons that may explain why our current methods of conducting behaviour change interventions struggle to achieve the changes we expect: 1) our current model for testing the efficacy or effectiveness of interventions tends to a mean effect size. This ignores individual differences in response to interventions; 2) our interventions tend to assume that everyone values health in the way we do as health professionals; and 3) the great majority of our interventions focus on addressing cognitions as mechanisms of change. We appeal to people's logic and rationality rather than recognising that much of what we do and how we behave, including our health behaviours, is governed as much by how we feel and how engaged we are emotionally as it is with what we plan and intend to do. Drawing on our team's experience of developing multiple interventions to promote and support health behaviour change with a variety of populations in different global contexts, this article explores strategies with potential to address these issues.